The impact of flexible working arrangements on work-life conflict and work pressure in Ireland - Helen Russell; Philip J. O'Connell; Frances McGinnity (The Economic and Social Research Institute (ESRI), 2007)
Recent rapid economic growth in Ireland has been accompanied by a strong surge in the number of women in employment, and this has led to a significant increase in the proportion of dual-earner families. These changes have brought the issue of reconciliation between work and care commitments to the fore. Flexible working arrangements in firms have been identified as one important means of balancing work and other commitments (Evans 2001). In this paper we investigate the relationship between four flexible working arrangements - flexi-time, part-time hours, working from home and job-share - and two key employee outcomes - work pressure and work-life conflict, using data from the first national survey of employees in Ireland in 2003. Our results show that while part-time work and flexi-time tend to reduce work pressure and work-life conflict, working from home is associated with greater levels of both work pressure and work-life conflict. We conclude that it is important to distinguish between flexible working arrangements to discover their potential for reducing work pressure and work-life conflict.
Keywords: 330; work-life balance; flexible working arrangements; gender; work stress; work pressure; Weibliche Arbeitskräfte; Arbeitsbedingungen; Stress; Arbeitsmarktflexibilität; Familie; Beruf; Geschlecht; Irland